Temporary labour migration and underdevelopment in Sri Lanka: the limits of remittance capital. (2nd September 2019) - Withers, Matt
ABSTRACT: Sri Lanka's long history of temporary labour migration to West Asia began amidst economic upheaval in 1977 and burgeoned during decades marred by macroeconomic volatility and ethnic conflict. Today, the remittances sent by migrant domestic workers and low-waged manual labourers in the Gulf are vital to the subsistence of poor households in marginalised communities and constitute the country's largest source of foreign exchange earnings. Prominent policymaking frameworks purport that temporary labour migration of this kind should produce a 'triple win' outcome, wherein remittance transfers catalyse economic development for migrant households and their countries of origin. Yet, while labour-receiving economies unequivocally benefit from exploiting reserve armies of labour and care, the developmental impact of inbound remittance flows remains under-theorised. This article advances a critique of how remittance capital functions at household, national and global scales to demonstrate how temporary labour migration has limited Sri Lanka to a precariously uneven and remittance-dependent model of development. A profound contradiction emerges where uneven development 'pushes' vulnerable populations into foreign employment, only for their remittances to sustain exclusionary development spending that intensifies the need to migrate.